Cross-Situational Self-Consistency in Nine Cultures: The Importance of Separating Influences of Social Norms and Distinctive Dispositions. (July 2017) - Locke, Kenneth D.; Church, A. Timothy; Mastor, Khairul A.; Curtis, Guy J.; Sadler, Pamela; McDonald, Kelly; Vargas-Flores, José de Jesús; Ibáñez-Reyes, Joselina; Morio, Hiroaki; Reyes, Jose Alberto S.; Cabrera, Helena F.; Mazuera Arias, Rina; et al.
We assessed self-consistency (expressing similar traits in different situations) by having undergraduates in the United States ( n = 230), Australia ( n = 220), Canada ( n = 240), Ecuador ( n = 101), Mexico ( n = 209), Venezuela ( n = 209), Japan ( n = 178), Malaysia ( n = 254), and the Philippines ( n = 241) report the traits they expressed in four different social situations. Self-consistency was positively associated with age, well-being, living in Latin America, and not living in Japan; however, each of these variables showed a unique pattern of associations with various psychologically distinct sources of raw self-consistency, including cross-situationally consistent social norms and injunctions. For example, low consistency between injunctive norms and trait expressions fully explained the low self-consistency in Japan. In accord with trait theory, after removing normative and injunctive sources of consistency, there remained robust distinctive noninjunctive self-consistency (reflecting individuating personality dispositions) in every country, including Japan. The results highlight how clarifying the determinants and implications of self-consistency requires differentiating its distinctive, injunctive, and noninjunctive components.